Estimation of the spectral distribution of X-ray beams by computational iterative calculation and dosimetry program design, using attenuation data - Castillo, Miguel (2019)
The present research has allowed us to determine the X-ray spectrum, for this we have designed a computational program through iterative calculation, samples of attenuation data have been taken and then a previously designed program has been used with a programming language, with the attenuation data. For our case we have worked with the Aluminum and Copper lters. This research has allowed us to: 1.- Find the spectra of X-ray radiation. 2.- Design a program that allows us to nd the X-ray spectra, which we must compare with the X-ray spectra previously determined by Tominaga (1981). 3.- Design a Visual X-ray Dosimetry Program. The expected result is the obtaining of the radiation spectra and the optimization of the X-ray dosimetry, based on the designed program.